Tafsir Tahlili: Sebuah Metode Penafsiran Al-Qur'an - Rosalinda Rosalinda (Hikmah: Journal of Islamic Studies, 2019)
Tafsir tahlili method is one of the method used by classical mufassir until now in interpreting al-Qur'an verses. This method emerges because of the necessity to the detail explanation of the instruction in the Al-Qur'an. This is also because of the increasing number of moslems along with the times, not only from the Arab nations but also from non-Arabic. Mufassir with tahlili method present an explanation of Al-Qur'an verses which are based on sequence of verses in the manuscripts (mushaf) of Al-Quran seen from any aspects, such as compatibility of one verse with another verse (munasabah al ayah), the cause of the descending verses, the meaning of verses globally, legal review contained, and additional explanation about qiroat, 'i'rab, and others. Keywords: Tafsīr Taḥlīlī , Method of Interpreting, Taḥlīlī Metode tafsir taḥlīlī merupakan salah satu metode yang digunakan oleh para mufassir klasik hingga kini dalam menjelaskan ayatayat al-Qur’an. Metode ini lahir karena kebutuhan terhadap penjelasan petunjuk al-Qur’an secara lebih rinci yang disebabkan kuantitas umat Islam yang semakin bertambah seiring perkembangan zaman, tidak hanya dari bangsa Arab saja tetapi juga non-Arab. Para mufassir dengan metode taḥlīlī menyajikan penjelasan ayat-ayat al-Qur’an berdasarkan urutan ayat dalam mushaf dilihat dari berbagai aspeknya, seperti munāsabah ayat, sebab turun ayat, makna ayat secara global, tinjauan hukum yang terkandung dan tambahan penjelasan tentang qira’at, i’rab dan lainnya. Keywords: Tafsīr Taḥlīlī , Metode Tafsīr, Taḥlīlī